2022
DOI: 10.18805/lr-4994
|View full text |Cite
|
Sign up to set email alerts
|

Host Plant Resistance and Analysis of Chemical Compounds Responsible for Bruchid Resistance in Greengram Vigna radiata (L.) Wilczek

Abstract: Background: Greengram Vigna radiata (L.) Wilczek, is an important legume crop that serves as a low-cost source of protein. The bruchid (Callosobruchus spp.) is a serious storage pest affecting greengram and other pulse crops. Thus, a study was designed to investigate bruchid resistance (Callosobruchus chinensis) in inter sub-specific derived lines of greengram and to identify chemical compounds responsible for resistance. Methods: The experimental material comprised of 200 inter sub-specific derived lines of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Several compounds have been identified to confer resistance against C. maculatus in cowpea, which include alkaloids, flavonoids, phenols, phenolic acids, and tannins (Kpoviessi et al, 2021; Lattanzio et al, 2005; Ojwang et al, 2012). Hema et al (2022) also identified 9, 12‐octadecadienoic acid, methyl ester; hexadecanoic acid, 1‐(hydroxymethyl)‐1,2‐ethanediylester, and hexadecanoic‐acid, 2‐oxiranyl methyl ester in mutant Vigna radiata resistant against C. chinensis in their study, suggesting an antibiosis mechanism. This inhibits larva development, thus preventing further destruction by larvae of the insect within the seeds (War et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Several compounds have been identified to confer resistance against C. maculatus in cowpea, which include alkaloids, flavonoids, phenols, phenolic acids, and tannins (Kpoviessi et al, 2021; Lattanzio et al, 2005; Ojwang et al, 2012). Hema et al (2022) also identified 9, 12‐octadecadienoic acid, methyl ester; hexadecanoic acid, 1‐(hydroxymethyl)‐1,2‐ethanediylester, and hexadecanoic‐acid, 2‐oxiranyl methyl ester in mutant Vigna radiata resistant against C. chinensis in their study, suggesting an antibiosis mechanism. This inhibits larva development, thus preventing further destruction by larvae of the insect within the seeds (War et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…Several compounds have been identified to confer resistance against C. maculatus in cowpea, which include alkaloids, flavonoids, phenols, phenolic acids, and tannins (Kpoviessi et al, 2021;Lattanzio et al, 2005;Ojwang et al, 2012). Hema et al (2022) The co-evolution of plants and their predators has resulted in phytophagous insects adaptation to the deterrent chemicals contained in the plants they feed on (Carlini & Grossi-De-Sá, 2002). Consequently, this may have led to the development of a more complex defense mechanism system against phytophagous insects such as the C. maculatus.…”
Section: Analysis Of Seed Storage Proteins and Seed Coat Compounds Th...mentioning
confidence: 99%